Diesel exhaust nanoparticles and their behaviour in the atmosphere. (21st December 2018) - Harrison, Roy M.; Rob MacKenzie, A.; Xu, Hongming; Alam, Mohammed S.; Nikolova, Irina; Zhong, Jian; Singh, Ajit; Zeraati-Rezaei, Soheil; Stark, Christopher; Beddows, David C. S.; Liang, Zhirong; Xu, Ruixin; et al.
Abstract : Diesel engine emissions are by far the largest source of nanoparticles in many urban atmospheres, in which they dominate the particle number count, and may present a significant threat to public health. This paper reviews knowledge of the composition and atmospheric properties of diesel exhaust particles, and exemplifies research in this field through a description of the FASTER project (Fundamental Studies of the Sources, Properties and Environmental Behaviour of Exhaust Nanoparticles from Road Vehicles) which studied the size distribution—and, in unprecedented detail, the chemical composition—of nanoparticles sampled from diesel engine exhaust. This information has been systematized and used to inform the development of computational modules that simulate the behaviour of the largely semi-volatile content of the nucleation mode particles, including consequent effects on the particle size distribution, under typical atmospheric conditions. Large-eddy model studies have informed a simpler characterization of flow around the urban built environment, and include aerosol processes. This modelling and engine-laboratory work have been complemented by laboratory measurements of vapour pressures, and the execution of two field measurement campaigns in London. The result is a more robust description of the dynamical behaviour on the sub-kilometre scale of diesel exhaust nanoparticles and their importance as an urban air pollutant.